Computationally Selected Epitopes: Integrated Approaches Toward High‐Affinity Artificial Protein Binders Obtained via Computationally Simulated Epitopes for Protein Recognition (Adv. Funct. Mater. 15/2019). (9th April 2019) - Altintas, Zeynep; Takiden, Aref; Utesch, Tillmann; Mroginski, Maria A.; Schmid, Bianca; Scheller, Frieder W.; Süssmuth, Roderich D.
Abstract : In article number1807332, Zeynep Altintas and co‐workers combine computational and experimental studies to develop high affinity artificial protein binders by targeting a cancer biomarker. The artificial receptors show excellent affinity toward the protein marker, even superior to that of state‐of‐the‐art antibodies.